Spectroscopic Assessment of Gold Nanoparticle Biodistribution Using Surface Plasmon Resonance Phenomena - Kim, Jiwon; Lee, Su-kyoung; Schellingerhout, Dawid; Nahrendorf, Matthias; Kim, Kwangmeyung; Kim, Jongseong; Kim, Dong-Eog (AMER CHEMICAL SOC, 2019)
Pharmacokinetic (PK) evaluation of nanomaterials are crucial for further clinical development of imaging nanomaterials. In spite of huge advances in nanoparticle-based biomedical research, PK assessment typically requires substantial resources. Here, we show a simple, inexpensive, and yet precise analytical method applicable to the PK interrogation of gold nanoparticles (AuNPs) in the body. We have developed a UV-vis spectroscopic technique that utilizes mechanochemical treatments to separate AuNPs from tissues and then employs surface plasmon of extracted AuNPs to quantify their distribution in the body. This method allows the detection of 10 mu g/mL of AuNPs in solution, as was confirmed by using inductively coupled plasma mass spectrometry. We demonstrate biodistribution of fibrin-targeted AuNPs that enable microCT-based visualization of arterial thrombi in mice: blood and thrombi as well as various organs. We believe that our method is generally applicable to most PK studies utilizing AuNPs in medical applications.